The Stability of Self-Control in a Population Representative Study - Deborah A. Cobb-Clark; Nancy Kong; Hannah Schildberg-Hörisch (Institute of Labor Economics (IZA), 2021)
We investigate the stability of self-control at the population level. Analyzing repeated Brief Self-Control Scale scores, we demonstrate that self-control exhibits a high degree of mean-level, rank-order, and individual-level stability over the medium term. Changes in self-control are not associated with major life events, nor are they economically important. The stability of self-control is particularly striking given our study period (2017-2020) spans the onset of the COVID-19 pandemic.
Keywords: D91; D01; 330; self-control; Brief Self-Control Scale; SOEP; stability